Novel GLA Mutation Promotes Intron Inclusion Leading to Fabry Disease - Varela, Patrícia; Caldas, Myrtes Martins; Pesquero, João Bosco (Frontiers in Genetics, 2019)
Fabry Disease (FD) is a rare and underdiagnosed X-linked disorder resulting from the deficient activity of the lysosomal hydrolase α-galactosidase A, leading to storage of complex glycosphingolipids inside of lysosomes in critical organs and tissues, impairing their functions and consequently resulting in a progressive multisystem disease. FD is caused by mutations in the GLA gene and only 4.8% of described mutations are located in the splice site regions. RNA splicing is an essential step to the formation of functional proteins and mutations in splice site regions can cause formation of aberrant transcripts leading to disease. Here we report a novel GLA insertion at position c.801+2_801+3 in intron 5 in a Brazilian family with suspicion of FD. The index case, a 46-year-old male, presented undetectable α-galactosidase A activity. Analysis of blood cDNA found two aberrantly GLA transcripts. In the first transcript, a novel donor splice site was created promoting formation of an intron inclusion with 37 bp. The splice site was not recognized in the second transcript and the intron 5 was not excised. The wild-type transcript was not formed and both aberrant transcripts lead to a premature stop codon. Despite not being in the canonical site, this new mutation disrupts existing 5’ splice site and produces two aberrantly transcripts leading to FD.